N6‐Methyladenosine Regulates Cilia Elongation in Cancer Cells by Modulating HDAC6 Expression - Yalan Rui; Haisheng Zhang; Kangning Yu; Shiyao Qiao; Chenglin Gao; Xiansong Wang; Weifeng Yang; Gholamreza Asadikaram; Zigang Li; Kun Zhang; Jianxin Peng; Jiexin Li; et al. (Advanced Science)
Abstract Primary cilia are microtubule‐based organelles that function as cellular antennae to address multiple metabolic and extracellular cues. The past decade has seen significant advances in understanding the pro‐tumorigenic role of N6‐methyladenosine (m6A) modification in tumorigenesis. Nevertheless, whether m6A modification modulates the cilia dynamics during cancer progression remains unclear. Here, the results show that m6A methyltransferase METTL3 regulates cilia length in cancer cells via HDAC6‐dependent deacetylation of axonemal α‐tubulin, thereby controlling cancer development. Mechanically, METTL3 positively regulates the translation of HDAC6 in an m6A‐dependent manner, while m6A methylation of A3678 in the coding sequence (CDS) of HDAC6 ameliorates its translation efficiency via facilitating the binding with YTHDF3. The upregulation of HDAC6 induced by METTL3 over‐expression is capable of inhibiting cilia elongation and acetylation of α‐tubulin, thereby shortening cilia length and accelerating the progression of cervical cancer both in vitro and in vivo. Collectively, depletion of METTL3‐mediated m6A modification leads to abnormally elongated cilia via suppressing HDAC6‐dependent deacetylation of axonemal α‐tubulin, ultimately attenuating cell growth and cervical cancer development.